A meta-analysis of genome-wide association studies for adiponectin levels in East Asians identifies a novel locus near WDR11-FGFR2 - Wu, Ying; Gao, He; Li, Huaixing; Tabara, Yasuharu; Nakatochi, Masahiro; Chiu, Yen-Feng; Park, Eun Jung; Wen, Wanqing; Adair, Linda S.; Borja, Judith B.; Cai, Qiuyin; Chang, Yi-Cheng; et al. (My University, 2014)
Blood levels of adiponectin, an adipocyte-secreted protein correlated with metabolic and cardiovascular risks, are highly heritable. Genome-wide association (GWA) studies for adiponectin levels have identified 14 loci harboring variants associated with blood levels of adiponectin. To identify novel adiponectin-associated loci, particularly those of importance in East Asians, we conducted a meta-analysis of GWA studies for adiponectin in 7827 individuals, followed by two stages of replications in 4298 and 5954 additional individuals. We identified a novel adiponectin-associated locus on chromosome 10 near WDR11-FGFR2 (P 3.0 10(14)) and provided suggestive evidence for a locus on chromosome 12 near OR8S1-LALBA (P 1.2 10(7)). Of the adiponectin-associated loci previously described, we confirmed the association at CDH13 (P 6.8 10(165)), ADIPOQ (P 1.8 10(22)), PEPD (P 3.6 10(12)), CMIP (P 2.1 10(10)), ZNF664 (P 2.3 10(7)) and GPR109A (P 7.4 10(6)). Conditional analysis at ADIPOQ revealed a second signal with suggestive evidence of association only after conditioning on the lead SNP (P-initial 0.020; P-conditional 7.0 10(7)). We further confirmed the independence of two pairs of closely located loci (2 Mb) on chromosome 16 at CMIP and CDH13, and on chromosome 12 at GPR109A and ZNF664. In addition, the newly identified signal near WDR11-FGFR2 exhibited evidence of association with triglycerides (P 3.3 10(4)), high density lipoprotein cholesterol (HDL-C, P 4.9 10(4)) and body mass index (BMI)-adjusted waisthip ratio (P 9.8 10(3)). These findings improve our knowledge of the genetic basis of adiponectin variation, demonstrate the shared allelic architecture for adiponectin with lipids and central obesity and motivate further studies of underlying mechanisms.